2004
DOI: 10.1088/0953-8984/16/49/021
|View full text |Cite
|
Sign up to set email alerts
|

Magnetodielectric effects in the ferroelectric ferromagnet BiMnO3

Abstract: The changes in the dielectric constant of perovskite BiMnO 3 at about T C , which are induced by the magnetic ordering as well as by the application of magnetic fields, indicate that coupling exists between the magnetism and the dielectric properties. The soft-mode theory based on the single-well potential model and the molecular-field approximation to the Heisenberg model are successfully applied to the electric and magnetic subsystems coexisting in the perovskitetype ferroelectromagnet BiMnO 3 , respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 30 publications
(39 reference statements)
0
33
0
Order By: Relevance
“…χ e (T ) exhibits a trend observed experimentally with increasing H a , but the calculated changes are too large. However, the corresponding temperature range is reproduced to much better accuracy than that of [20], where the calculated temperature T RM is far too low. The magnetic-susceptibility data follow roughly the Curie-Weiss law with the paramagnetic Curie temperature Θ M ≈ 120K.…”
Section: Magnetic Propertiesmentioning
confidence: 85%
See 2 more Smart Citations
“…χ e (T ) exhibits a trend observed experimentally with increasing H a , but the calculated changes are too large. However, the corresponding temperature range is reproduced to much better accuracy than that of [20], where the calculated temperature T RM is far too low. The magnetic-susceptibility data follow roughly the Curie-Weiss law with the paramagnetic Curie temperature Θ M ≈ 120K.…”
Section: Magnetic Propertiesmentioning
confidence: 85%
“…(19)(20) it directly effects the rapid increase of electric polarization and magnetization in ordered state and is the greatest possible value for the coupling.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The orbital structure will be described using a model of electron vibrational (vibronic) interactions as described by the following Hamiltonian [12,13]: (2) Let us consider partial contributions stipulated by this model. The main linear contribution from the near est neighbor oxygen environment of manganese ion can be written as and V e = -1.29 eV/Å is the linear vibronic interaction constant determined in [14].…”
Section: Crystalline and Orbital Structures Of Bimnomentioning
confidence: 99%
“…Bismuth manganite BiMnO 3 has been treated in many investigations as a multiferroelectric compound [1][2][3][4][5][6]. However, the results of recent experiments [7,8] have shown that this ferromagnetic crystal belongs to the C2/c symmetry group, which excludes the exist ence of spontaneous polarization [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%